Niat Menggunakan Kembali Jasa Pengiriman Pos Express Ditinjau Dari Kualitas Layanan, Kemudahan, Dan Lokasi Di Surabaya - Jahroni, Jahroni; Saleh, Ade Surya (Universitas Muhammadiyah Gresik, 2025)
Abstract Background - In the era of digital and globalization that is increasingly developing, the public's need for goods delivery services has increased significantly. Expedition service companies are required to provide fast, safe, and reliable services. Pos Express as one of the premium services from PT Pos Indonesia strives to answer this need through fast H+1 delivery and an integrated tracking system. However, based on data from Top Brand Indonesia, Pos Indonesia is still below its competitors such as JNE, J&T, and TIKI, indicating the need for improvements in terms of service quality, ease of access, and location strategy. This phenomenon underlies the importance of this study, considering that consumers are now increasingly demanding efficiency and convenience in using delivery services. Objectives - This study aims to analyze and test the effect of service quality, ease of use, and location on consumer intentions in Surabaya in using Pos Express delivery services. This study also aims to identify which factors are most dominant in forming intentions to use the service. Design / Methodology / Approach - This research employs a quantitative approach through a survey method. The participants consisted of Surabaya residents who had previously used Pos Express services, with a purposively selected sample of 100 respondents. Data were collected using questionnaires and analyzed through multiple linear regression to examine the relationships between variables. To validate the regression model, several classical assumption tests were conducted, including tests for normality, multicollinearity, heteroscedasticity, and autocorrelation. Findings - The findings show that reuse intention is positively and significantly influenced by three independent factors, namely service quality, convenience, and location. Among the three, service quality has the most dominant influence, followed by location and convenience. The R² value of 66.2% indicates that the model can explain more than half of the variation in reuse intention. Research Implications - The results of this study contribute to the literature on service marketing management, especially in the context of logistics and delivery. These findings can be the basis for PT Pos Indonesia management in designing strategies to improve service quality, develop user-friendly digital systems, and select more strategic operational locations, in order to increase consumer intention to reuse Pos Express services. Research Limitations - This study is limited to the Surabaya area and only involves respondents who have experience using Pos Express delivery services. Therefore, the selection of respondents was carried out purposively, with the main criteria that they must have used Pos Express services in order to provide relevant assessments of the variables studied.